Save the Quinolones! Impact of a Non-Restrictive Fluoroquinolone Reduction Initiative on Antibiotic Use and Resistance at an Urban Teaching Hospital. (October 2022) - Smoke, Steven M.; Plotkin, Slava; Patel, Neeki; Hilden, Patrick
Background: Many antibiotic stewardship programs have sought to reduce fluoroquinolone use due to their association with a myriad of negative consequences. In hospital settings with fewer resources, initiatives that are less labor intensive may offer a more feasible approach to addressing fluoroquinolone use and improving patient care. Objective: This study assessed the impact of a non-restrictive fluoroquinolone reduction initiative on antibiotic use and resistance. Methods: This was a retrospective pre- and post-interventional ecological study conducted from 2016 to 2017. The fluoroquinolone reduction initiative consisted of education on risks and alternatives. Buttons promoting "Save the Quinolones" were also worn to increase visibility. Outcome measures were the rate of fluoroquinolone use and antibiotic resistance in Staphylococcus aureus, Escherichia coli, Proteus mirabilis, Klebsiella pneumoniae, and Pseudomonas aeruginosa before and after the intervention. Results: Overall, fluoroquinolone use decreased throughout the study, but there was a significantly greater rate of decrease in the post-intervention period (monthly decrease of 3.3% (1.3, 5.1) v. 7.4% (5, 9.8) p = 0.043). S. aureus susceptibility to oxacillin increased from 47.2% to 55.2% (difference 8.0, 95%CI 1.2 to 14.7). P. aeruginosa susceptibility to levofloxacin increased from 60% to 70.7% (difference 10.7, 95%CI 0.8 to 20.6). No differences in susceptibility rates of E. coli, P. mirabilis or K. pneumoniae were detected. Conclusion: This non-restrictive fluoroquinolone reduction initiative led to a significant decrease in fluoroquinolone use that was associated with decreased antibiotic resistance in S. aureus and P. aeruginosa.